Co‐Located Wind and Temperature Observations at Mid‐Latitudes During Mesospheric Inversion Layer Events - Mariaccia, A.; Keckhut, P.; Hauchecorne, A.; Khaykin, S.; Ratynski, M. (Geophysical research letters, 2023)
The mesospheric inversion layer (MIL) phenomenon is a temperature enhancement (10–50 K) in a vertical layer (∼10 km) lasting several days and spanning thousands of kilometers within the mesosphere. As MILs govern the mesospheric variability, their study is crucial for a better understanding of the middle‐atmosphere global circulation. MIL phenomenon is also important for applications in aeronautics as perturbations in the mesosphere are significant issues for the safe reentry of rockets, space shuttles, or missiles. However, the description of this phenomenon remains incomplete, since no observations of MIL's effects on winds exist, hampering an understanding of the mechanisms responsible for their formation. This study investigates simultaneous wind‐temperature observations in the altitude range of 30–90 km during MIL events. Strong winds deceleration occurred in the same altitude range as the temperature inversion, confirming the role of gravity waves in MIL's formation mechanisms. Plain Language Summary Atmospheric waves propagate from the lower to upper layers, transferring their energy throughout the atmosphere. The mesosphere (50–90 km) is subject to these energy transfers, causing unexpected temperature increases (10–50 K) over a vertical layer (∼10 km). These deviations are called mesospheric inversion layers (MILs). Though largely observed in temperature profiles, the MIL phenomenon remains misunderstood, as MIL's impacts on the wind in the middle atmosphere remain unknown. In this study, we first reported simultaneous wind‐temperature observations between 30 and 90 km during MIL events. We observed a strong wind deceleration in the same altitude range where the temperature increases. This result argues in favor of the role of gravity waves in MIL's formation mechanisms. Key Points First simultaneous wind and temperature observations in the altitude range 30–90 km during mesospheric inversion layer events According to these new observations, there is a strong wind deceleration occurring at the same altitude that the temperature inversion These results argue in favor of the mesospheric inversion layer's formation mechanism involving gravity wave dissipation